Gomorphological Observations on Sermersôq. A Contribution to the Geomorphology of S. Greenland. - Soen, Oen Ing (Meddelelser om Grønland, 1965)
On the island of Sermersôq four erosion surfaces have been recognized, which are of regional importance in S Greenland. Their development is related to three cycles of erosion, interrupted by two glacial stages. The high-level erosion surface at altitudes above 1000 m is the remnant of an old peneplane, which was formed during the oldest erosion cycle and uplifted in late Cretaceous or early Tertiary times. This uplift initiated a second erosion cycle in the course of which a main glacial stage intervened. In this glacial stage the ice-level in the main valleys (the present fjords) acted as the effective base level of erosion and this resulted in the formation of stretches of an intermediate-level erosion surface, which now occur along the main fjords at altitudes between 400 m and 650 m. An important lowering of effective base level of erosion occurred when in the subsequent interglacial stage the sea-level resumed its role as the effective base level of erosion. This event initiated a third erosion cycle in the course of which the low-level erosion surface, between 100 m and 250 m altitude, and the strandflat, a coastal platform below 50 m, were formed. The third erosion cycle was interrupted by a second glacial stage, which on Sermersôq has the localized character of a mountain glaciation; it is during this second glacial stage that the present day fretted upland morphology of central Sermersôq originated. Post-glacial vertical movements causing the emergence of the strandflat induced a rejuvenation of erosion and consequently the incision of this coastal platform and valley floors by recent rivers.